Measurement systems and sensors - Nawrocki, Waldemar (Artech House, 2016)
This thoroughly updated and expanded second edition is an authoritative resource on industrial measurement systems and sensors, with particular attention given to temperature, stress, pressure, acceleration, and liquid flow sensors. This edition includes new and expanded chapters on wireless measuring systems and measurement control and diagnostics systems in cars. Moreover, the book introduces new, cost-effective measurement technology utilizing www servers and LAN computer networks - a topic not covered in any other resource.nnCoverage of updated wireless measurement systems and wireless GSM/LTE interfacing make this book unique, providing in-depth, practical knowledge. Professionals learn how to connect an instrument to a computer or tablet while reducing the time for collecting and processing measurement data. This hands-on reference presents digital temperature sensors, demonstrating how to design a monitoring system with multipoint measurements. From computer-based measuring systems, electrical thermometers and pressure sensors, to conditioners, crate measuring systems, and virtual instruments, this comprehensive title offers engineers the details they need for their work in the field.n Publisher abstract.
Keywords: Electronic instruments.; Measurement.; Detectors.; Electronic apparatus and appliances.; elektronické knihy; electronic books